Microwave a.c. conductivity of domain walls in ferroelectric thin films - Alexander Tselev; Pu Yu; Ye Cao; Liv R. Dedon; Lane W. Martin; Sergei V. Kalinin; Petro Maksymovych (Nature Communications, 2016)
Conducting charged ferroelectric domain walls, as potential building blocks for future electronic devices, are unstable and uncommon in ferroelectric materials. Here, Tselev et al. show that neutral insulating domain walls in PbZrO3 and BiFeO3thin films are conductive under microwave excitation, allowing for non-destructive read-out.